Intonation as a Medium of Individual‘s Perception and Expression - Oleinik, Helen (Respectus Philologicus, 2005)
The article is concemed with a psychological aspect of intonation. The intonation parameters and theircombinations convey the infonnation about the psychological state and features of the speaker.To establish the type of relationship between intonation and psychological features was one of the aims of theresearch. The findings of the experiment enable to state that 1) the listener can perceive the psychologicalfeatures of the speaker with a certain degree of correctness based on the intonation parameters; 2) a definitetype of co “elation exists between certain intonation parameters, a psychological state and psychological features.The carried research singled out 1) the factors determining the listener’s identification of the speaker’spsychological features and 2) the intonation models manifesting the speaker’s psychological state.
Keywords: correlation of the intonation and the psychological state; the intonation models of psychological states; perception; intonation parameters; identification of the psychological features of the speaker on the basis of intonation